2015
DOI: 10.1089/hgtb.2014.122
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Shearing Linear Amplification Polymerase Chain Reaction: An Improved Method for Quantifying Lentiviral Vector Insertion Sites in Transplanted Hematopoietic Cell Systems

Abstract: In gene therapy trials targeting blood disorders, it is important to detect dominance of transduced hematopoietic stem cell (HSC) clones arising from vector insertion site (VIS) effects. Current methods for VIS analysis often do not have defined levels of quantitative accuracy and therefore can fail to detect early clonal dominance. We have developed a rapid and inexpensive method for measuring clone size based on random shearing of genomic DNA, minimal exponential PCR amplification, and shear site counts as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Individual vector insertion sites were identified with the use of the quantitative shearing linear amplification (qsLAM) PCR method. 22…”
Section: Vector Copy Number and Insertion-site Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Individual vector insertion sites were identified with the use of the quantitative shearing linear amplification (qsLAM) PCR method. 22…”
Section: Vector Copy Number and Insertion-site Analysismentioning
confidence: 99%
“…Vector integration site analysis of lineage-sorted blood cells obtained from Patients 1 through 7 at 6 to 21 months after infusion was performed with the use of a qsLAM PCR assay 22 ; integration site analysis of the 6-month sample from Patient 8 is in progress, and the results were not available at the time of this report. Unique vector-genome junctions provide clonal markers for each originally transduced hematopoietic progenitor, and the frequency of each unique junction sequence is a measure of the clonal proliferation.…”
Section: Vector Integration Site Analysismentioning
confidence: 99%
“…Although some of the published protocols for retroviral integration site analysis use the LM-PCR approach, none of the available protocols was designed to accurately identify rare integration sites in samples from HIV infected individuals on therapy. For example, there are two published protocols for retroviral integration site analysis that were designed primarily for use with samples obtained from gene therapy patients [43,45]. Although both protocols are similar ours, there are, in both cases, important differences.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, these data relied primarily on the identification of viral integration sites (VIS). Recently developed methods (Zhou, Bonner et al 2014) have shown all VIS in a sample can now be recovered, although previous percentages recovered were much lower (60-80%) (Schmidt, Schwarzwaelder et al 2007), (Kustikova, Baum et al 2008), (Gabriel, Eckenberg et al 2009). Nevertheless, quantification of clone numbers based on sequencing reads is inherently imprecise (Cornils, Bartholomae et al 2013), (Brugman, Suerth et al 2013).…”
Section: Human Blood Cell Production Barcoding Experiments: Making Thmentioning
confidence: 99%